Managing Marcus Gunn Ptosis - Our Approach - A. K. Grover; Shaloo Bageja (Delhi Journal of Ophthalmology)
Marcus Gunn ptosis is a congenital synkinetic ptosis due to an abnormal innervation of the levator muscle. Aim of the surgical treatment is to eliminate jaw winking phenomenon and correct ptosis. Moderate to severe jaw winking ptosis is best corrected by excision of the levator aponeurosis with frontalis suspension. Bilateral levator excision with bilateral fascia lata suspension gives the most symmetrical and aesthetically pleasing results. The surgical technique is highlighted in the article.